Far-ultraviolet irradiation at 222 nm destroys and sterilizes the biofilms formed by periodontitis pathogens - Jun Nishikawa; Tomohiro Fujii; Soichiro Fukuda; Shoma Yoneda; Yuta Tamura; Yuki Shimizu; Akie Yanai; Yuki Kobayashi; Koji Harada; Keisuke Kawasaki; Katsuaki Mishima; Kenji Watanabe; et al. (Journal of Microbiology, Immunology and Infection, 2024)
Background: Periodontal disease is the leading cause of tooth loss, and an association between periodontal disease and non-oral systemic diseases has been shown. Formation of biofilm by periodontal pathogens such as Fusobacterium nucleatum, Porphyromonas gingivalis, and Streptococcus mutans and their resistance to antimicrobial agents are at the root of persistent and chronic bacterial infections. Methods: The bactericidal effect of far-ultraviolet (F-UV) light irradiation at 222 nm on periodontal bacteria was assessed qualitatively and quantitatively. The effect of biofilm disruption by F-UV light on periodontal bacteria was examined by crystal violet staining, and the morphologic changes of the biofilm after F-UV irradiation were explored by confocal laser microscopy and scanning electron microscopy. We developed a thin fiber-type 222 nm F-UV irradiator and studied its safety and effect of reducing bacteria in rodent models. Results: F-UV light at 222 nm had a bactericidal effect on F. nucleatum, P. gingivalis, and S. mutans. Irradiation with F-UV light reduced the biofilm formed by the bacteria and sterilized them from within. Confocal laser microscopy showed a clear reduction in biofilm thickness, and scanning electron microscopy confirmed disintegration of the biofilm architecture. F-UV irradiation was less damaging to DNA and less cytotoxic than deep-ultraviolet light, and it reduced bacterial counts on the tooth surface. Conclusion: F-UV irradiation has the potential to destroy biofilm and act as a bactericide against pathogenic bacteria in the biofilm.